2012
DOI: 10.1519/jsc.0b013e31825c2c9b
|View full text |Cite
|
Sign up to set email alerts
|

Kettlebell Swing Training Improves Maximal and Explosive Strength

Abstract: The aim of this study was to establish the effect that kettlebell swing (KB) training had on measures of maximum (half squat-HS-1 repetition maximum [1RM]) and explosive (vertical jump height-VJH) strength. To put these effects into context, they were compared with the effects of jump squat power training (JS-known to improve 1RM and VJH). Twenty-one healthy men (age = 18-27 years, body mass = 72.58 ± 12.87 kg) who could perform a proficient HS were tested for their HS 1RM and VJH pre- and post-training. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 18 publications
2
64
1
1
Order By: Relevance
“…Therefore, applying these results to subject populations with differing kettlebell exercise experience may not be appropriate. However, it should also be noted the recent research has shown 2-handed swing exercise with relatively light loads (12-16 kg) by relatively untrained subjects (kettlebell exercise specifically and resistance exercise in general) demonstrated significant improvements in maximum and explosive strength after six weeks (11). The final limitation that should be considered is that this study considered mechanical output data derived from ground reaction force.…”
Section: A C C E P T E Dmentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, applying these results to subject populations with differing kettlebell exercise experience may not be appropriate. However, it should also be noted the recent research has shown 2-handed swing exercise with relatively light loads (12-16 kg) by relatively untrained subjects (kettlebell exercise specifically and resistance exercise in general) demonstrated significant improvements in maximum and explosive strength after six weeks (11). The final limitation that should be considered is that this study considered mechanical output data derived from ground reaction force.…”
Section: A C C E P T E Dmentioning
confidence: 91%
“…It would appear that the net product of these mechanisms results in arrival at the brakingpropulsion phase transition immediately preceded by an eccentric braking phase that requires the generation of vertical force that is sufficient to arrest continued negative displacement of the CM, which, in turn is greater than the starting force of non-SSC movement (3,4). This could go some way to explain how six weeks of 2-handed swing exercise improved vertical jump performance (11), and must be considered by strength and conditioning coaches when they select exercises for athlete strength and conditioning programs.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor hip strength also correlates with proneness to fatigue in patients with chronic lower-back pain in comparison to healthy control subjects during a sustained back extension endurance test [3]. In addition to meeting the demands of daily activity, hip extension movement is becoming more attractive in sports training as it is [12]. However, studies using the HTT method to improve these two areas of performance are limited.…”
mentioning
confidence: 99%